Microstructure and dielectric properties of Yttrium Iron Garnet-Strontium Titanate bi-plates junctions and composites junctions - Wong, Swee Yin (2017)
In this project, the investigation towards morphology and dielectric properties of single sample Strontium Titanate (ST) and Yttrium Iron Garnet (YIG), ST-YIG composite slabs (SYCS) and ST-YIG composites (SYC) were carried out. This is a pioneer work since no reports or studies were found on dielectric-magnetic slabs. Each slab is made up of ST and YIG sample where for one slab, the samples were prepared via mechanical alloying (MA) method while the other were prepared via conventional solid state (SS) method. X-ray Diffraction (XRD) was employed for phase identification and purity of the samples. Since the ST-YIG composites prepared were multiphase, Rietveld refinement method was used to estimate the phase composition in each sample. MA method successfully reduced the sintering temperature for the reaction to occur at a much lower temperature compare to SS method. The surfaces of the sample were visualized using Field emission scanning electron microscopy (FESEM) and the average grain size was calculated. From FESEM images, MA method produced very fine particles in nano-scale while SS method in micro-scale. The slabs were sintered at 1300oC with different sintering hours from 10 hours to 20 hours at intervals of 2 hours for SS method whereas for MA method, it was sintered at 1200oC. The samples for the slab were co-joined strongly through diffusional processes where no welding was involved. The junction properties were studied. FESEM images were also taken of the cross-sectional area of the slab and the diffusion of ST into YIG and vice versa can be observed at the junction. This only occurs for the slab prepared via SS method. The diffusion depth of both samples of the composite slab was determined via EDX. The distance at the junction where the ions moved from one compound to the other during the diffusion process is calculated. Movement of ions in the samples is dependent on the different sintering hours. However, for the slab prepared via MA method, a slight diffusion occurs but the samples do not stick together. This is probably due to the continuous network of grain in YIG which only indicated the initial stage of sintering. The increased on migration of grain boundary increased the driving force for neck growth. Since surface diffusion and lattice diffusion dominated, therefore no interdiffusion process happened on the surface contact of ST and YIG. Thus, interstitial lattice diffusion among ST and YIG were difficult to obtain. To understand the charge stored and energy dissipated, the dielectric properties of samples were investigated. Since the samples are multi-phase, hence the dielectric constant obtained is a contribution from different phases. Generally, the dielectric constant of the samples increases with the rise in temperature and decreases with frequency. The samples prepared via SS method have the best dielectric properties among the samples possibly due to the fine grain size of ST with large grain size of YIG produced denser grains by increasing the insulating grain boundary volume. For the slabs prepared via SS method, the dielectric constant and dielectric loss factor follows the trend of YIG rather than ST. The slabs produced better dielectric properties with higher value of dielectric constant and lower dielectric loss factor compared with single sample YIG. Therefore, it may be useful in microwave applications such as tunable HTS (high temperature superconducting) microwave filters. Analysis using complex modulus was also done on the samples to verify the polarization mechanism involved in the samples and slabs.